2002
DOI: 10.3201/eid0803.010192
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Antimicrobial Use and Antimicrobial Resistance in Europe

Abstract: In Europe, antimicrobial resistance has been monitored since 1998 by the European Antimicrobial Resistance Surveillance System (EARSS). We examined the relationship between penicillin nonsusceptibility of invasive isolates of Streptococcus pneumoniae (an indicator organism) and antibiotic sales. Information was collected on 1998-99 resistance data for invasive isolates of S. pneumoniae to penicillin, based on surveillance data from EARSS and on outpatient sales during 1997 for beta-lactam antibiotics and macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
333
0
24

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 608 publications
(373 citation statements)
references
References 19 publications
8
333
0
24
Order By: Relevance
“…Therefore it is essential to introduce multidisciplinary interventions to reduce the inappropriate use of antibiotics to increase the lifespan of precious antibiotics. Studies have shown a relationship between Papers excessive use of antibiotics, antimicrobial resistance and benefits of control [17].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is essential to introduce multidisciplinary interventions to reduce the inappropriate use of antibiotics to increase the lifespan of precious antibiotics. Studies have shown a relationship between Papers excessive use of antibiotics, antimicrobial resistance and benefits of control [17].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing concern regarding the resistance to uropathogens to antibiotics. The clinical impact of drug resistance may be great or insignifi cant, depending on the level of resistance, the site of infection, and the availability of eff ective, nontoxic therapeutic alternatives 7 . This prospective study was conducted to identify UTI due to multidrug resistant uropathogens among children and to evaluate empiric antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, studies combining data from the European Surveillance of Antimicrobial Consumption and EARSS showed that there was a high degree of consistency between β -lactam use and the rate of resistance in S. pneumoniae isolates. Rates of antibiotic resistance that were higher in southern and central Europe than in northern Europe were shown to be related to higher consumption of antibiotics in southern and central Europe (Bronzwaer et al 2002;Goossens et al 2005;Sande-Bruinsma et al 2008). In Japan, no database for antimicrobial prescriptions at the national or regional level is currently available.…”
Section: Discussionmentioning
confidence: 99%